Emotional and cognitive experiences during the time of diagnosis and decision-making following a prenatal diagnosis: a qualitative study of males presented with congenital heart defect in the fetus carried by their pregnant partner - Tommy Carlsson; Elisabet Mattsson (BMC, 2018)
Abstract Background Expectant fathers consider the second-trimester obstetric ultrasound examination as an important step towards parenthood, but are ill prepared for a detection of a fetal anomaly. Inductive research is scarce concerning their experiences and needs for support. Consequently, the aim of this study was to explore the emotional and cognitive experiences, during the time of diagnosis and decision-making, among males presented with congenital heart defect in the fetus carried by their pregnant partner. Methods Twelve expectant fathers were consecutively recruited through two tertiary referral centers for fetal cardiology in Sweden, after they had been presented with a prenatal diagnosis of congenital heart defect in the fetus carried by their pregnant partner. The respondents were interviewed via telephone, and the interviews were analyzed using inductive qualitative content analysis. Results The respondents experienced an intense emotional shock in connection with detection. However, they set their own needs aside to attend to the supportive needs of their pregnant partner, and stressed the importance of an informed joint decision regarding whether to continue or terminate the pregnancy. When terminating the pregnancy, they experienced a loss of a wanted child, an emotionally intense termination procedure, needs of support neglected by professionals, and worries about the risk of recurrence in future pregnancies. When continuing the pregnancy, they tried to keep a positive attitude about the coming birth, but were simultaneously worried about the postnatal situation. Conclusions The findings illustrate the importance of inclusive care and adequate follow-up routines for both expectant parents following a prenatal diagnosis. This includes the initial emotional shock, the decisional process, and depending on decision reached, the termination or continuation of the pregnancy. Expectant fathers presented with a fetal anomaly need adequate follow-up routines to address worries about risk of recurrence in future pregnancies and worries about the postnatal situation.